PSYCHOALYSIS OF CHARACTERS AND MORAL VALUES IN THE NOVEL KEPANGGANG WIRANG (BURNED ABOVE THE SHAME) BY TIWIEK SA - Rhian Ardila Maretin Lanua; Kundharu Saddhono; Supana Supana (IJOTL-TL: Indonesian Journal of Language Teaching and Linguistics, 2017)
& This study describes characters and moral values in the Javanese Novel entitled Kepanggang Wirang (Burned Above the Shame) by Tiwiek SA.  Description dealt with psycholiguical needs in accordance with Abraham Maslow theory and educational values.  This study is qualittaive research and applied psychoanalysis as the research design.  Data were collected using contant analysis and interview and were analyzed using content analysis that included: taxonomy, domain, and thematic analyses.  The study revealed that psychological needs from Maslow including: sex, security, self-esteem, and love and affection, and self-actualization were present in the novel.  In addition, moral values having positive and negative perspectives were conveyed in the novel reflecting experiences in the society the readers should have considered in the real community lifes. .